Maternal demographics and hemodynamics for the prediction of fetal growth restriction at booking, in pregnancies at high risk for placental insufficiency. (3rd January 2016) - Stott, Daniel; Bolten, Mareike; Salman, Mona; Paraschiv, Daniela; Clark, Katherine; Kametas, Nikos A.
Abstract: Introduction: Fetal growth restriction (FGR) is associated with poor perinatal outcomes. Screening and prevention tools for FGR, such as uterine artery Doppler imaging and aspirin, underperform in high‐risk groups, compared with general antenatal populations. There is a paucity of sensitive screening tests for the early prediction of FGR in high‐risk pregnancies. Materials and Methods: This was a prospective observational study based in a dedicated antenatal hypertension clinic at a tertiary UK hospital. We assessed maternal demographic and central hemodynamic variables as predictors for FGR in a group of women at high risk for placental insufficiency due to chronic hypertension ( n = 55) or a history of hypertension in a previous pregnancy ( n = 71). Outcome variables were birthweight z‐score as well as development of FGR (defined as birthweight below the 5th or 3rd centile). Maternal hemodynamics were assessed using a noninvasive transthoracic bioreactance monitor (Cheetah NICOM). Results: The mean gestation at presentation was 13.6 (range: 8.5–19.5) weeks. Sixteen women delivered babies below the 5th centile. Ten of these were below the 3rd centile. Independent predictors of birthweight z‐score were body surface area, peripheral vascular resistance and white ethnicity ( R 2 = 0.26, p < 0.0001). Independent predictors of FGR were maternal height and cardiac output. The area under the receiver operator characteristic curve for prediction of FGR was 0.915 (95% CI 0.859–0.972) and 0.9079 (95% CI 0.823–0.990) for FGR below the 5th and 3rd centiles, respectively. Conclusion: In women with chronic hypertension or a history of hypertension in a previous pregnancy, maternal size and cardiac output at booking provide a sensitive screening tool for FGR.